An evaluative study on the role of primary school library services in promoting student literacy - Putrisolichat, Shafa Nurul Azmi; Hadiapurwa, Angga; Wulandari, Yayu (Jurnal Informatio, 2026)
Background: School libraries are often underutilised as centres of learning and literacy development, despite their great potential to support the educational process. The gap between the ideal function of libraries and the actual practice of library services in the field necessitates an evaluation that focuses on users’ real experiencesPurpose: This study aims to evaluate the role of libraries in increasing students’ interest in literacy at Labschool Elementary School UPI Bandung and to identify obstacles in the implementation of existing literacy programs. Methods: This research used field research with an evaluative approach using a goal-free evaluation model. The research subjects included 20 fourth-grade students as survey respondents and library managers as interview informants. Data collection techniques included a three-level Likert-scale survey to measure students’ literacy interest and semi-structured interviews to explore the condition of library services. Data analysis was conducted descriptively to interpret student responses and field findings. Results: The results showed that most students responded neutrally to the school-organised literacy activities. Conclusion: The literacy programs have not been fully able to foster students’ interest in reading optimally. Library services are still dominated by the function of providing Reading materials without the development of innovative and participatory literacy programs.